Navigating Legal Transformation: Challenges and Prospects of Cybernotary in Enhancing Public Service Efficiency in Indonesia - Lestari, Sulistyani Eka; Thoif, Mokh; Widodo, Teguh Endi; Minan, Minan (JURNAL AKTA, 2024)
The concept of cybernotary represents a transformative shift in the notary's role in the digital era, utilizing technology to enhance the efficiency and accessibility of legal services in Indonesia. While cyber notary holds potential for supporting the digitalization of notarial services and meeting the demands of modern society, its implementation in Indonesia encounters significant challenges, particularly in regulatory alignment and limited digital infrastructure. This study aims to provide a deeper understanding of how cyber notary supports the transformation of public services, making them faster, more efficient, and transparent, as well as to identify obstacles that must be overcome to achieve optimal implementation within state institutions. This research employs a qualitative approach, aimed at uncovering an in-depth understanding of e-Notarization's role in strengthening the digitalization process and enhancing the effectiveness of public services by state institutions. From a regulatory perspective, although there is a legal basis permitting electronic transactions, adequate technical and operational guidelines are still lacking to ensure smooth implementation. These challenges are particularly apparent in provisions requiring physical presence for the validation of signatures and fingerprints, which restrict the flexibility of notaries in serving the public digitally. As a result, these regulations constitute a principal barrier to the goals of cyber notary in delivering faster, more efficient, and more accessible legal services.